2005
DOI: 10.1007/s11172-005-0436-8
|View full text |Cite
|
Sign up to set email alerts
|

Cubane derivatives 7. Synthesis and molecular structure of 4-bromo-1-hydroxymethylcubane

Abstract: The present study concerned with reduction of methyl 4 bromocubanecarboxylate (1) with lithium aluminum hydride and aluminum hydride in THF. An efficient procedure was devel oped for the synthesis of 4 bromo 1 hydroxymethylcubane (2) based on reduction of com pound 1 with aluminum hydride under mild conditions. The structure of 2 was established by X ray diffraction.Key words: methyl 4 bromocubanecarboxylate, 4 bromo 1 hydroxymethylcubane, hydroxymethylcubane, reduction, lithium aluminum hydride, aluminum hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Therefore, this linear stacking can only indicate the potential interactions between the cubane scaffolds. The structure of 4‐bromo‐1‐(hydroxymethyl)cubane ( 50 ) shows the alcohol moiety in a linear hydrogen bonding fashion (Figure S23) . This allows the bromine atoms to interact with the hydrogen of the cubane in the next layer to create a 3D lattice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this linear stacking can only indicate the potential interactions between the cubane scaffolds. The structure of 4‐bromo‐1‐(hydroxymethyl)cubane ( 50 ) shows the alcohol moiety in a linear hydrogen bonding fashion (Figure S23) . This allows the bromine atoms to interact with the hydrogen of the cubane in the next layer to create a 3D lattice.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of 4-bromo-1-(hydroxymethyl)cubane( 50)s hows the alcohol moietyi nalinear hydrogen bondingf ashion ( Figure S23). [25] This allows the bromine atoms to interact with the hydrogen of the cubane in the next layer to create a3 Dl attice.W hen substituting hydroxymethyl for a methyl nitrate (51)t he NO 2 group interacts with the cubane the CH 2 hydrogen atoms. [12a] This leaves bromine atoms close to each other to form ad irecth alogen-bonded network (Figure S24).…”
Section: Halogensmentioning
confidence: 99%
“…Previously, 5, 6 it has been shown that the reduction of dimethyl cubane 1,4 dicarboxylate (1a) and methyl 4 bromocubane 1 carboxylate (2) afforded 1,4 bis (hydroxymethyl)cubane (3) and 4 bromo 1 hydroxy methylcubane (4). In the present work, 1,4 bis(nitroxy methyl)cubane (5) and 4 bromo 1 nitroxymethylcubane (6) (Scheme 1) were synthesized for the first time and characterized.…”
Section: Methodsmentioning
confidence: 71%